2010
DOI: 10.1029/2010gc003090
|View full text |Cite
|
Sign up to set email alerts
|

Time‐averaged paleomagnetic field at the equator: Complete data and results from the Galapagos Islands, Ecuador

Abstract: [1] We present here the complete paleomagnetic laboratory results from a collection of approximately 1500 oriented cores from all 16 of the Galapagos Islands, Ecuador, collected by Allan Cox in 1964-1965 but nearly all previously unpublished. The islands are located in the eastern Pacific Ocean within 1.4°of latitude from the equator and range in age from historically erupted to 3 Ma, mostly determined by published K-Ar and 3 He isotopic dating. The number of sites collected on each island ranges from 1 to 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
(250 reference statements)
1
6
0
Order By: Relevance
“…2D) Islands that formed over the past ∼3 My (13), during which the Nazca plate moved east-southeast relative to the presumed Galapagos hot spot. The dispersed lava sites on different islands ensure a random temporal sampling over this time period (14,15). Previous alternating field (AF) (16) and thermal demagnetization (TD) (13) studies showed shallow average paleomagnetic directions (AF mean I = 1.9°± 3.0°; TD mean I = 2.3°± 3.0°) from 51 lava sites, which agree with the GAD hypothesis.…”
Section: Significancesupporting
confidence: 77%
“…2D) Islands that formed over the past ∼3 My (13), during which the Nazca plate moved east-southeast relative to the presumed Galapagos hot spot. The dispersed lava sites on different islands ensure a random temporal sampling over this time period (14,15). Previous alternating field (AF) (16) and thermal demagnetization (TD) (13) studies showed shallow average paleomagnetic directions (AF mean I = 1.9°± 3.0°; TD mean I = 2.3°± 3.0°) from 51 lava sites, which agree with the GAD hypothesis.…”
Section: Significancesupporting
confidence: 77%
“…The equatorial intercept ( a ) of the model curve for the Johnson et al () data (Figure a) is essentially controlled by the two low‐latitude PSV estimates from Costa Rica ( S b = 14 ° , Cromwell et al, ; Johnson et al, ) and Ecuador ( S b = 17.2 ° , Opdyke et al, ). Data subsequently collected from other localities within 10° of the equator (Gromme et al, ; Kent et al, ; Opdyke et al, , ) showed somewhat lower values of VGP dispersion ( S b < 13 ° , Figure b), which led Opdyke et al () to suggest that the results from Costa Rica and Ecuador may have been affected by unrecognized tectonic disturbances (tilting) in these actively deforming regions, resulting in artificially higher dispersion than expected on the basis of the results from tectonically quiescent low‐latitude sites. Because Opdyke et al () and Cromwell et al () included the Johnson et al () data in their compilations, and because their results suggest very similar patterns for the latitude behavior of PSV, we consider that the work of Opdyke et al () and Cromwell et al () supersedes the results of Johnson et al ().…”
Section: Discussionmentioning
confidence: 97%
“…The equatorial intercept (a) of the model curve for the Johnson et al (2008) data (Figure 14a) is essentially controlled by the two low-latitude PSV estimates from Costa Rica (S b = 14°, Cromwell et al, 2013;Johnson et al, 2008) and Ecuador (S b = 17.2°, Opdyke et al, 2006). Data subsequently collected from other localities within 10°of the equator (Gromme et al, 2010;Kent et al, 2010;Opdyke et al, 2010Opdyke et al, , 2015 showed somewhat lower values of VGP dispersion (S b < 13°, Figure 14b), which led Opdyke et al (2015) to suggest that the results from Costa Rica and Ecuador may have been affected by unrecognized tectonic disturbances (tilting) in these actively deforming regions, resulting in artificially higher dispersion than expected on the basis…”
Section: Applicability Of Model G For Describing the Latitude Behaviomentioning
confidence: 99%
“…The Galápagos archipelago comprises approximately 128 named islands and islets formed about three million years ago. The age of the islands increases moving from west to east because of the drift of the Nazca tectonic plate away from the East Pacific Ridge to the southeast over a hotspot [6][7][8]. This study was located in the southeastern highlands of San Cristóbal, the easternmost and one of the oldest islands in the Galápagos.…”
Section: Study Areamentioning
confidence: 98%